1973
DOI: 10.1136/bmj.4.5884.82
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind Cross-over Study of Ketoprofen and Ibuprofen in Management of Rheumatoid Arthritis

Abstract: SummaryA double-blind cross-over study of ketoprofen (Orudis) 150 mg daily and ibuprofen (Brufen) 1,200 mg daily was carried out in 35 outpatients with rheumatoid arthritis. Results suggest that analgesic and anti-inflammatory activity of ketoprofen is superior to that of ibuprofen. Significantly greater pain relief (P < 0 05) and reduction in joint circumference (P <0-01) was obtained with ketoprofen than with ibuprofen. Side effects of the drugs were comparable and pot serious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…To the best of our knowledge this is the first report of the potential clinical and structural benefit of the use of Acthar Gel in the management of early RA References: [1] Acthar Gel Package Insert. [2] Levine, Drug Design, Development and Therapy 2012:6. Background: Corticosteroids (CS) are used on rheumatoid arthritis (RA) treatment for decades, due to their rapid and efficacious improvement of arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge this is the first report of the potential clinical and structural benefit of the use of Acthar Gel in the management of early RA References: [1] Acthar Gel Package Insert. [2] Levine, Drug Design, Development and Therapy 2012:6. Background: Corticosteroids (CS) are used on rheumatoid arthritis (RA) treatment for decades, due to their rapid and efficacious improvement of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence related to the melanocortin system suggests that ACTH may have mechanisms of action in addition to steroidogenesis. (2) ACTH by virtue of inhibitory influences on cytokine action and inflammatory cell migration has been reported to be effective in multiple inflammatory disorders in humans and adrenalectomized rats (3). This may have significant relevance in the management of inflammatory disorders such as RA.…”
mentioning
confidence: 99%
“…In rheumatoid arthritis, double-blind within-patient trials have shown ketoprofen to have analgesic and anti-inflammatory activity greater than that of placebo (Cathcart et al, 1973;Zutshi et al, 1973) and of ibuprofen (Mills et al , 1973) and indistinguishable from that of an equal daily dose of indomethacin (Gyory et al, 1972). In patients with osteoarthrosis of the hip, the clinical efficacy of ketoprofen 100 mg daily was again indistinguishable from that of 100 mg daily of indomethacin (Gyory et al, 1972).…”
Section: Therapeutic Trialsmentioning
confidence: 99%
“…In controlled trials conducted to date comparing the therapeutic efficacy of ketoprofen with that of placebo, ibuprofen or indomethacin, each drug has been given in random order for a period of 1 (Cathcart et al, 1973) or 2 weeks (Gyory et al, 1972;Mills et al, 1973;Zutshi et al, 1973). All studies have excluded patients with renal or hepatic disease and most have also excluded those with a history of gastro-intestinal disease, as well as children, and women of childbearing age in whom the possibility of pregnancy could not be excluded.…”
Section: Controlled Trials In Rheumatoid Arthritismentioning
confidence: 99%
“…Upper abdominal pain or indigestion are the main complaints [3,4], Twenty-nine percent of the patients on NSAIDs had experienced heartburn, indigestion or sour stomach at least once within the previous week [5]. These gastrointestinal symptomatic complaints are important as they interfere with compliance and continuing use of NSAIDs.…”
Section: Introductionmentioning
confidence: 99%